Hallucinations in Guillain-Barré syndrome after cervical spine surgery: one case report - Yuan-yuan GUO; Hu SUN; Wen LI; Ya BAI; Shi-jing LI; Xue-dong LIU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
DOI: 10.3969/j.issn.1672-6731.2015.08.015